PERAN SOSIAL LAKI-LAKI DAN PEREMPUAN PERSPEKTIF AL-QUR’AN - Tohirin Tohirin; Zamahsari Zamahsari (Profetika: Jurnal Studi Islam, 2021)
One of the fundamental aspects that characterize human beings is gender. Allah SWT created humans with male and female sex (QS. Al-Hujurat [49]: 13). This difference has consequences for the differences in character, rights and obligations between men and women. This research is a library research (liberary research) with a qualitative exploratory approach. Researcher try to find a broad and deep understanding of an object so that later a hypothesis can be found and then formulated in a theory. The data source of this research is the verses of the Qur'an which relate to gender, especially those related to differences in roles, rights and obligations between men and women. The results of this study indicate that men and women from the perspective of the Koran are not merely biological identities. Male and female are terms intended to denote the different characteristics, duties and roles of each other's presence on earth. Men are characterized by characteristics of aggressiveness and independence, while women are characterized by tenderness, obedience, and love to decorate. The main duties and roles of men are matters relating to public affairs, especially with regard to leadership and earning a living (economic sector). Meanwhile, the main duties and roles of women are related to domestic affairs, especially with regard to childcare issues.